2015
DOI: 10.1021/acs.orglett.5b02705
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Synthesis of Functionalized Tetrahydroacridinones: Insights into a Mechanistic Route

Abstract: A mechanistic study of three-component reactions of various aromatic amines with a number of aldehydes and 1,3-diones was achieved. The unprecedented reaction involved a nucleophilic attack of an aromatic amine on the in situ generated Michael adduct intermediate followed by six-electron ring cyclizations. It is contrary to the common belief that advocates involvement of coupling reactions between a Knoevenagel adduct and an aromatic amine to deliver substituted tetrahydroacridinones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…S1 ) , appear in high‐field region, which can be assigned to the alkyl protons in dimedone moieties (corresponding assignment of these signals can be tracked in Supporting Information Fig. S1) . As can be seen in the 13 C NMR spectrum of M1 (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…S1 ) , appear in high‐field region, which can be assigned to the alkyl protons in dimedone moieties (corresponding assignment of these signals can be tracked in Supporting Information Fig. S1) . As can be seen in the 13 C NMR spectrum of M1 (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 79%
“…In the parallel experiment, the reaction conversion was much lower without the involvement of ammonium acetate, suggests the crucial role ammonium acetate played here. According to previous literatures, the 1,3‐dione was converted to enol‐form firstly and then via Knoevenagel condensation followed by Michael addition to get the target molecule . The introduction of ammonium acetate might facilitate the formation of enol‐form of 5,5‐dimethylcyclohexane‐1,3‐dione and sequentially promoted the reaction.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, the mechanistic studies on the multicomponent reactions was reported in literature under basic conditions that involve the nucleophilic attack of an amine on the in situ generated Michael adduct intermediate followed by six‐electron ring cyclization . It is contrary to the common belief of the accepted mechanistic route.…”
Section: Resultsmentioning
confidence: 98%
“…Compared with the reported method for three‐component reactions between 4‐methoxybenzaldehyde, dimedone, and various amines for synthesis of the desired tetrahydroacridines in literature , the present methodology demands shorter reaction time (5–20 min vs. 16–24 h), lower temperature (50 vs. 75°C), and much more efficient use of energy to offer the same or higher yield (Table ).…”
Section: Resultsmentioning
confidence: 99%